Editorial [ Hot Topic:Emerging Anticancer Effects of Antiresorptive Therapies (Guest Editor: Vera Hirsh)] - Hirsh, Vera (Anti-Cancer Agents in Medicinal Chemistry, 2012)
The past few decades have witnessed remarkable changes in the management of patients with cancer. Although more patients than ever before are being diagnosed with cancer, the survival rate for patients with cancer has increased substantially [1]. The refined use of surgical strategies, conventional cytotoxic agents, and radiotherapy and the development of targeted agents have been integral components of this success across the different malignancies. However, with increased survival came the emergence of skeletal complications (that had previously been common mostly in the last few months of life for patients with cancer [eg, hypercalcemia of malignancy and fractures]) in patients with life expectancies of several months to years. Advances in supportive care have offered improved pain management, more effective antiemetic and antidiarrheal medications [2,3], refined palliative radiotherapeutic strategies (including bone-seeking radionuclides) [4], and the application of bisphosphonate therapy to prevent cancer treatment-induced bone loss and reduce the risk of skeletal-related events from bone metastases [5]. In the past 2 years, with the emergence of evidence that, in addition to their established supportive care roles, bisphosphonates appear to also possess clinically meaningful anticancer activity, the fields of anticancer therapy and supportive care have partially merged. In this Hot Topics edition of Anticancer Agents in Medicinal Chemistry, the clinical development of bisphosphonates in the oncology setting is reviewed in detail (Widler et al., p. X), and the emerging anticancer data for this class of agents are discussed (Clézardin, p. X). Recent data releases from database analyses and ongoing trials of bisphosphonates have demonstrated their potential to provide benefits beyond supportive care. These potential benefits are especially robust in the early disease setting—and may even extend to cancer prevention (Chlebowski and Col, p X.). The manuscripts in this edition therefore review the rationale for the elevation of bisphosphonates from adjunctive palliative agents to anticancer therapies in their own right. Early evidence for this in advanced cancer settings first emerged with zoledronic acid in the genitourinary cancers (as reviewed by Saad and Mulders, p. X), as well as in lung cancer and solid tumors other than breast and prostate cancer (as reviewed in my manuscript, p. X). However, the potential for clinical anticancer effects with the other bisphosphonates in patients with metastatic disease is unknown. It is likely that differences between bisphosphonates will come to light as further trial data emerge. Most recently, Morgan et al., [6] reported that zoledronic acid is superior to clodronate not only for the prevention of skeletal-related events but also for improving overall and progression-free survival in patients with newly diagnosed multiple myeloma (as reviewed by Terpos, p. X). Further information is expected from ongoing comparative trials, especially in the early breast cancer setting, wherein zoledronic acid has already demonstrated benefits beyond those achievable with endocrine therapy alone in randomized controlled trials (as reviewed by Gnant, p. X). The role of bisphosphonates and the choice of which agent to utilize in each of the oncology settings is expected to evolve as data from the ongoing studies mature. However, given the wealth of clinical experience with these agents and their favorable overall tolerability profile of these agents, the anticancer potential of bisphosphonate therapy is likely to remain a hot topic in the next few years....